HIRUDINELLA VENTRICOSA (TREMATODA) PARASITIZING MAKAIRA NIGRICANSANDACANTHOCYBIUM SOLANDRI FROM NEOTROPICAL REGION, BRAZIL - Nunes Felizardo, Nilza (2013)
In January 2002, were caught 11 Makaira nigricansLacepède, 1802 (Istiophoridae) and two Acanthocybium solandri(Cuvier, 1832) (Scombridae) off Cabo Frio municipality, Rio de Janeiro State, Brazil. We collected digenetic trematodes from the stomach of some of these fishes. We studied these trematodes with optical and scanning electron microscopy and identified them as Hirudinella ventricosa(Pallas, 1774) Baird, 1835. This is the first report of this species in A. solandriin the Brazilian coast, and in M. nigricansin South America.